Preparation of Amorphous SnO2‐Encapsulated Multiphased Crystalline Cu Heterostructures for Highly Efficient CO2 Reduction - Yin, Peng‐Fei; Fu, Jiaju; Yun, Qinbai; Chen, Bo; Liu, Guigao; Li, Lujiang; Huang, Zhiqi; Ge, Yiyao; Zhang, Hua (Advanced materials (Weinheim), 2022)
Controlling the architectures and crystal phases of metal@semiconductor heterostructures is very important for modulating their physicochemical properties and enhancing their application performances. Here, a facile one‐pot wet‐chemical method to synthesize three types of amorphous SnO2‐encapsulated crystalline Cu heterostructures, i.e., hemicapsule, yolk–shell, and core–shell nanostructures, in which unconventional crystal phases (e.g., 2H, 4H, and 6H) and defects (e.g., stacking faults and twin boundaries) are observed in the crystalline Cu cores, is reported. The hemicapsule Cu@SnO2 heterostructures, with voids that not only expose the Cu core with unconventional phases but also retain the interface between Cu and SnO2, show an excellent electrocatalytic CO2 reduction reaction (CO2RR) selectivity toward the production of CO and formate with high Faradaic efficiency (FE) above 90% in a wide potential window from −1.05 to −1.55 V (vs reversible hydrogen electrode (RHE)), and the highest FE of CO2RR (95.3%) is obtained at −1.45 V (vs RHE). This work opens up a new way for the synthesis of new heterostructured nanomaterials with promising catalytic application. Three types of Cu@SnO2 nanostructures with hemicapsule, yolk–shell, and core–shell architectures are synthesized, in which a series of unconventional phases of Cu (i.e., 2H, 4H, and 6H) is observed. The obtained hemicapsule heterostructures exhibit superior CO2 reduction reaction selectivity toward CO and formate with high Faradaic efficiency (above 90%) in a wide potential window, outperforming their yolk–shell and core–shell counterparts.